Baghdad Sufis In the book of obituaries (Journal of the College of Basic Education, 2022)
It is not known exactly when Sufism began in the Islamic state and who was the first Sufi, although most of the Sufi names were from the East, and we are not here to study the Sufi beliefs, because they are developed and different between one Sufi and another, so our research will be limited to the Baghdadi Sufis in the book Deaths of Notables, Because the study of all the Baghdadi Sufis requires a wide and intensive space that these pages cannot accommodate, in addition to the translations of those Baghdadis about whom Ibn Khalkan wrote () (d. 681 AH / 1282 CE) did not touch on their sayings in oneness - that is, that the individual reaches the station of God and Lord As in the rest of the books, although there are certainly exceptions, such as the translation of al-Hallaj (d. 309 AH / 921 CE), for example, but we will confine ourselves to the Baghdadis because the translation does not need interpretation and interpretation of the hadiths contained in it.